2018
DOI: 10.1038/s41598-018-33599-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of host pathways universally inhibited after Plasmodium yoelii infection for immune intervention

Abstract: Malaria is a disease with diverse symptoms depending on host immune status and pathogenicity of Plasmodium parasites. The continuous parasite growth within a host suggests mechanisms of immune evasion by the parasite and/or immune inhibition in response to infection. To identify pathways commonly inhibited after malaria infection, we infected C57BL/6 mice with four Plasmodium yoelii strains causing different disease phenotypes and 24 progeny of a genetic cross. mRNAs from mouse spleens day 1 and/or day 4 post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Many negative regulators of IFN-I response were found, likely due to sampling mRNA relatively late (day 4 pi) after malaria infection. In order to search for potential receptors in IFN-I signaling, here we performed Ts-eQTL analysis using new mRNA samples collected from spleen tissues during early infection (24 h pi) (28) and again identified a large number of gene clusters based on GPLSs (Dataset S1A). Among the clusters were those containing Toll-like receptors (TLR2, 3, 4, 7, 8, 9, 11, 12, and 13) and DDX58 (RIG-I), suggesting activation of various innate immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Many negative regulators of IFN-I response were found, likely due to sampling mRNA relatively late (day 4 pi) after malaria infection. In order to search for potential receptors in IFN-I signaling, here we performed Ts-eQTL analysis using new mRNA samples collected from spleen tissues during early infection (24 h pi) (28) and again identified a large number of gene clusters based on GPLSs (Dataset S1A). Among the clusters were those containing Toll-like receptors (TLR2, 3, 4, 7, 8, 9, 11, 12, and 13) and DDX58 (RIG-I), suggesting activation of various innate immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the authors noted that the expression of five genetically regulated human leukocyte antigen (HLA) class II loci was negatively correlated with parasite load and molecules such as IL18R1, TLR4, TLR5, IFNGR1, and IFNGR2, suggesting impairment of antigen processing and immune signaling. Impairment of antigen processing and T cell activation, including suppression of various MHCII genes, were also observed in C57BL/6 mice infected with different P. yoelii strains and progeny of a P. yoelii genetic cross (Xia et al, 2018). In a dual transcriptome analyses of the host and parasite genes in samples from 46 malaria-infected Gambian children, Lee et al (2018) performed multivariate analyses and showed association of disease severity with increased expression of granulopoiesis and IFN-γ related genes as well as inadequate suppression of IFN-I signaling (Lee et al, 2018).…”
Section: Transcriptome Analysis Of Patient Samplesmentioning
confidence: 92%
“…Malaria parasites trigger an immune response the moment when they enter a host. To survive in this hostile environment, the parasite displays a range of strategies to evade host killing mechanisms, including variations in antigen epitopes targeted by host immune machinery and interference or suppression of specific arms of the host immune response (Recker et al, 2011;Yam and Preiser, 2017;Larsen et al, 2018;Xia et al, 2018). One of the consequences of these host-parasite interactions is increased genetic diversity at genes encoding proteins under host immune selection ( Figure 3A), leading to genetic signatures of diversifying selection in the parasite genome.…”
Section: Host-parasite Interaction and Evolution Highly Polymorphic Imentioning
confidence: 99%
“…Most pathogens adopt two strategies for modifying their surface protein expression to bypass detection by a host's immune system: changing some antigens' expression in an “on-off” fashion and by expressing different forms of a particular antigen (Deitsch et al, 2009). Most P. falciparum strain has sequence differences and variable expression levels regarding exposed antigens to avoid antibody recognition (Schofield and Mueller, 2006; Wu et al, 2014; Xia et al, 2018). These mechanisms enable a parasite's immune evasion and the emergence of clinical immunity, manifest by the absence of clinical symptoms.…”
Section: The Host's Immune Response Can Induce Changes In Invasion LImentioning
confidence: 99%
“…These mechanisms enable a parasite's immune evasion and the emergence of clinical immunity, manifest by the absence of clinical symptoms. A parasite's chronic exposure to a host facilitates its adaptation mechanisms, decreasing parasitaemia, changing its invasion phenotype and modulating erythrocyte invasion ligand expression, making itself invisible to a host's immune system (Schofield and Mueller, 2006; Persson et al, 2008; Xia et al, 2018); immune evasion is therefore crucial for parasite survival, establishing chronic infection and transmission.…”
Section: The Host's Immune Response Can Induce Changes In Invasion LImentioning
confidence: 99%